Regulatory Lymphocytes Are Key Factors in MHC-Independent Resistance to EAE. (27th April 2014) - Marín, Nieves; Mecha, Miriam; Espejo, Carmen; Mestre, Leyre; Eixarch, Herena; Montalban, Xavier; Álvarez-Cermeño, José C.; Guaza, Carmen; Villar, Luisa M.
Abstract : Background and Objectives . Resistant and susceptible mouse strains to experimental autoimmune encephalomyelitis (EAE), an inducible demyelinating experimental disease serving as animal model for multiple sclerosis, have been described. We aimed to explore MHC-independent mechanisms inducing resistance to EAE. Methods . For EAE induction, female C57BL/6 (susceptible strain) and CD1 (resistant outbred strain showing heterogeneous MHC antigens) mice were immunized with the 35–55 peptide of myelin oligodendrocyte glycoprotein (MOG35−55 ). We studied T cell proliferation, regulatory and effector cell subpopulations, intracellular and serum cytokine patterns, and titers of anti-MOG serum antibodies. Results . Upon immunization with MOG35−55, T lymphocytes from susceptible mice but not that of resistant strain were capable of proliferating when stimulated with MOG35−55 . Accordingly, resistant mice experienced a rise in regulatory B cells (P = 0.001 ) and, to a lower extent, in regulatory T cells (P = 0.02 ) compared with C57BL/6 susceptible mice. As a consequence, MOG35−55 -immunized C57BL/6 mice showed higher percentages of CD4+ T cells producing both IFN-gamma (P = 0.02 ) and IL-17 (P = 0.009 ) and higher serum levels of IL-17 (P = 0.04 ) than resistant mice. Conclusions . Expansion of regulatory B and T cells contributes to the induction of resistance to EAE by an MHC-independent mechanism.